A Project feasibility study on the manufacture of sanitary panties - Javier, Jonamelle; Sacramento, Christine; Montoya, Luis; Espiritu, Frances (College of Engineering, 1989)
Using principles acquired from past courses, the group shall develop a project through a feasibility study. It proposes to put up a company that would manufacture Sanitary Panties. A sanitary panty is an undergarment that would supplement the needs of a woman during her menstrual period. It would provide added protection which sanitary napkins and tampons cannot give, because of this feature; the product can be classified as a luxury item. The group aptly calls the product "NO FLOW". The study focused on the National Capital Region as its area of study, all data such as prices, wage rates, population etc. would apply only to the mentioned area. Preliminary research showed that there was no readily available data on undergarments, much less on sanitary panties. A market survey was conducted to properly analyze the market. Using stratified sampling with occupation and geographical location as the stratification variables, a total of 391 students, working women and housewives were given questionnaires. Their ages range from 14 to 51. The survey showed that there is a demand for the product in the National Capital Region. The specifications of the product was finalized, it would be a plastic-lined panty made of cotton. It is to be constructed with an additional cotton material on the inner face of the crotch to avoid contact between the plastic lining and the skin, thus providing protection against allergies and rashes. Further research indicated that there exist three brands of locally produced sanitary panties; Supply is estimated at 15,000 dozens or 180,000 pieces. Comparing the demand and the supply, the group found out that the product would be able to easily enter the market, provided that intensive advertising is employed. Producing this product is similar to introducing a new product. The target market will consist of students and working women from the upper middle class to the upper class. And to capture this market, the proposed selling price is P30, based on a prestige pricing scheme. This price is not too far away from the survey's resulting price range. After determining the market, it was necessary to determine the technical feasibility. Since the firm would be dealing with only one product line, the appropriate form of business organization is the single proprietorship. Under a President/General Manager, there would be four divisions: Purchasing, Sales and Marketing, Production and Accounting. The basis of the technical study is the production schedule. Expected sales of the first year of production are estimated at 30% of the projected demand of the Market Analysis. This percentage would go up as a result of the advertising campaigns and it would reach its peak on the fourth and fifth years. Then sales would be expected to decrease as the competition realizes the size of the market and because of innovations on the sanitary napkin. Materials needed to produce are found to be locally available, although the equipment needed is imported. Technically, the production process is simple and therefore feasible. The product shall go through work stations with minimal transportation and delay. After considering three alternative locations, the group chose the San Francisco Del Monte, Quezon City site. The site is accessible to both distribution centers and suppliers. All essential utilities needed for production are available. The existing building is sufficient for office and factory space requirements. The existing area has a provision for possible expansion. The final layout shows that there will be a straight line flow from raw material storage, through the work stations to the finished goods storage. There would be five workstations, determined by the machines to be sued for production. Two machines of each kind are needed to meet the daily requirements. After considering all technical aspects, total project cost was estimated to approximately be P 3M. The business would be financed by the owner and through a loan. From Pro Forma Financial Statements, the average Return on Investment was computed to be 60%, a high value. Sensitivity Analysis shows that sales level has a safety margin of 70% while selling price has a 27% margin. Further calculations revealed that profit is most sensitive to price and leas at to fixed costs. The economical desirability of the product was measured in terms of the benefit-cost ratio; it was calculated to be 35.76. The benefits include employment and government revenue generated by the project while the cost to society was the cost of equipment, which are all imported from Japan. The group therefore concludes that the project is feasible with respect to market, technical, financial feasibility and social profitability.